264TiPENGOT-ov43/KEYLYNK-001: A phase III trial of pembrolizumab plus chemotherapy with olaparib maintenance for first-line treatment of BRCA¬-nonmutated advanced epithelial ovarian cancer. (24th November 2019) - Fujiwara, K; Vergote, I B; Sehouli, J; Salutari, V; Zola, P; Madry, R; Wenham, R M; Korach, J; Pautier, P; Cibula, D; Lheureux, S; Hasegawa, K; et al.
Abstract: Background: Epithelial ovarian cancer (EOC) is the most lethal gynecologic cancer and is often diagnosed at advanced stages. The current standard of care (SOC) for advanced EOC is primary debulking surgery (PDS) followed by adjuvant carboplatin/paclitaxel chemotherapy (CT). Although SOC may be effective initially, most patients experience relapse within 3 years after treatment. Combination therapy with PD-1 inhibitor pembrolizumab (pembro) plus PARP inhibitor niraparib resulted in efficacy in patients with platinum-resistant, relapsed OC in the phase 1/2 study TOPACIO/KEYNOTE-162. The PARP inhibitor olaparib is approved for women with newly diagnosed BRCA-mutated OC, as well as for platinum-sensitive, recurrent OC regardless of BRCA1/2 status. Pembro plus CT followed by olaparib maintenance therapy is being investigated in ENGOT-ov43/KEYLYNK-001 (NCT03740165), a phase 3, randomized, double-blind, active- and placebo-controlled study for first-line treatment of women with BRCA1/2-nonmutated advanced EOC. Trial design: Women with stage III or IV BRCA-nonmutated EOC, primary peritoneal cancer, or fallopian tube cancer will be randomized 1:1:1 after one lead-in cycle of CT to receive pembro + CT followed by olaparib maintenance; pembro + CT followed by placebo; or placebo + CT followed by placebo. Stratification factors include surgery status (residual tumor after PDS [yes/no] or planned interval debulking), planned bevacizumab use (yes/no), and PD-L1 combined positive score (CPS; <10 or ≥ 10). Pembro 200 mg Q3W will be administered for 35 infusions and CT will be administered for 5 cycles. Twice-daily olaparib 300 mg maintenance therapy will start after the end of CT as concomitant treatment with pembro for 2 years if the patient has a complete response or until discontinuation. Bevacizumab use is determined at the investigator's discretion before randomization. Primary endpoints are investigator-assessed PFS per RECIST 1.1 criteria and OS. Key secondary endpoints are PFS assessed per RECIST 1.1 by blinded independent central review, PFS after next-line treatment, and safety. Enrollment is currently ongoing. Clinical trial identification: NCT03740165. Legal entity responsible for the study: Merck & Co., Inc. Funding: Funding for this study was provided by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: K. Fujiwara: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Chugai Pharma; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Eisai; Advisory / Consultancy, Research grant / Funding (institution): Merck Sharpe & Dohme Corp.; Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Taiho Pharmaceutical; Advisory / Consultancy: Takeda; Honoraria (self): Bayer; Honoraria (self): Daiichi Sankyo; Honoraria (self): Janssen Oncology; Honoraria (self): Kyowa Hakko Kirin; Honoraria (self), Research grant / Funding (institution): Lilly Japan; Honoraria (self): Nippon Kayaku; Honoraria (self), Research grant / Funding (institution): Ono Pharmaceutical; Honoraria (self): Zeria Pharmaceutical; Research grant / Funding (institution): GlaxoSmithKline; Research grant / Funding (institution): Immunogen; Research grant / Funding (institution): Kaken Pharmaceutical; Research grant / Funding (institution): Oncotherapeutics; Research grant / Funding (institution): Shionogi. I.B. Vergote: Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy: Eisai; Advisory / Consultancy, Travel / Accommodation / Expenses: PharmaMar; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Advisory / Consultancy: Advaxis; Advisory / Consultancy: Merck Sharp & Dohme Corp.; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Genmab; Advisory / Consultancy: Millennium Pharmaceuticals; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: Immunogen; Advisory / Consultancy, Travel / Accommodation / Expenses: TESARO, Inc.; Advisory / Consultancy, Research grant / Funding (institution): Oncoinvent; Advisory / Consultancy: Roche; Advisory / Consultancy: Sotio; Travel / Accommodation / Expenses: Takeda; Research grant / Funding (institution): Amgen. J. Sehouli: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self): Eisai; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Clovis; Honoraria (self): Olympus; Honoraria (self): Johnson&Johnson; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: PharmaMar; Honoraria (self): Teva Pharmaceutical Industries Ltd.; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: TESARO, Inc.; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Merck Sharpe & Dohme Corp.; Advisory / Consultancy: Lilly; Advisory / Consultancy, Travel / Accommodation / Expenses: Roche. P. Zola: Advisory / Consultancy, Travel / Accommodation / Expenses: TESARO, Inc.; Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy, Research grant / Funding (self): Roche. R.M. Wenham: Research grant / Funding (self), Shareholder / Stockholder / Stock options: Ovation Diagnostics; Advisory / Consultancy, Speaker Bureau / Expert testimony: TESARO, Inc.; Advisory / Consultancy: Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony: Clovis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Genentech; Advisory / Consultancy: Mersana Therapeutics; Research grant / Funding (self): TapImmune; Research grant / Funding (self): Merck; Research grant / Funding (self): Prescient Therapeutics. P. Pautier: Advisory / Consultancy: Roche; Advisory / Consultancy, Travel / Accommodation / Expenses: PharmaMar; Advisory / Consultancy: GlaxoSmithKline. S. Lheureux: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): TESARO, Inc.; Research grant / Funding (institution): Roche/Genentech; Research grant / Funding (institution): Regeneron. K. Hasegawa: Honoraria (self), Research grant / Funding (self): Daiichi-Sankyo; Honoraria (self): Chugai; Honoraria (self), Advisory / Consultancy: Merck Sharpe & Dohme Corp.; Honoraria (self): AstraZeneca; Research grant / Funding (self): Yakult Honsha; Research grant / Funding (self): Pfizer. C-H. Lai: Research grant / Funding (self): Roche; Research grant / Funding (self): TTY Biopharm. A. Gonzalez-Martinez: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy: Clovis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Merck Sharpe & Dohme Corp.; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): TESARO, Inc.; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pharmama. Q. Liu: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. S.M. Keefe: Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. M. Puglisi: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. All other authors have declared no conflicts of interest.